2017
DOI: 10.3390/ma10030256
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ultrasound Treatment on Cavitation Erosion Resistance of AlSi7 Alloy

Abstract: Ultrasound treatment of liquid aluminum alloys is known to improve mechanical properties of castings. Aluminum foundry alloys are frequently used for production of parts that undergo severe cavitation erosion phenomena during service. In this paper, the effect of the ultrasound treatment on cavitation erosion resistance of AlSi7 alloy was assessed and compared to that of conventionally cast samples. Cavitation erosion tests were performed according to ASTM G32 standard on as-cast and heat treated castings. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 53 publications
3
22
1
Order By: Relevance
“…The non-dendritic structure can be easily achieved by stirring the alloy while cooling it from the liquid state down into the semi-solid temperature range. This results in a suspension consisting of a liquid metallic phase and primary solid particles with globular or rosette-type shape [2,3], such as that shown in Figure 1, in comparison with a typical dendritic microstructure. The rheological properties of this special type of slurry give the advantages of the semi-solid metals (SSM)-processing.…”
Section: Introductionmentioning
confidence: 99%
“…The non-dendritic structure can be easily achieved by stirring the alloy while cooling it from the liquid state down into the semi-solid temperature range. This results in a suspension consisting of a liquid metallic phase and primary solid particles with globular or rosette-type shape [2,3], such as that shown in Figure 1, in comparison with a typical dendritic microstructure. The rheological properties of this special type of slurry give the advantages of the semi-solid metals (SSM)-processing.…”
Section: Introductionmentioning
confidence: 99%
“…At this regard, some authors report the hardness as an indicator of the erosion resistance. Nevertheless, these models reached limited success in prediction erosion damage, as well as the attempt to correlate cavitation resistance and hardness [14][15]. Damage due to cavitation can occur also on various aluminum automotive components, as such as cylinders and pistons, combustion chambers, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the family of wrought alloys, various alloys belonging to the Al-Cu, Al-Mg, Al-Si-Mg or Al-Zn-Mg families were tested in different conditions [14,17] taking also into account the influence of real erosion environments, as for instance the presence of aggressive fluids or slurries [8,18]. For casting alloys, in general, it was found that Al alloys resistance is strongly affected by several microstructural properties, as such as grain size, number of interfaces between different phases, presence and morphology of secondary phases [14][15][19][20]. This is not surprising since various studies report the influence of eutectic [21][22] and intermetallic phase [23][24][25], as well as the role of grain size [26][27], on other mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Other damaging mechanisms of SSM components have been investigated over the years, such as cavitation resistance [110,111]. It was reported that the globular microstructure, as obtained by ultrasound treatment methods (UTS), increases the cavitation erosion resistance of the alloy because of the higher chemical and microstructural homogeneity, the morphology of the primary particles, and the refined structure of the eutectic due to the treatment itself.…”
Section: Wear Resistancementioning
confidence: 99%
“…Surface topographies of the damaged areas of conventionally as-cast (a) before and (b) after T6, semi-solid in (c) as-cast and (d) after T6[111].…”
mentioning
confidence: 99%